Formation of sporadic-E (Es) layers under the influence of AGWs evolving in a horizontal shear flow. (December 2015) - Didebulidze, G.G.; Dalakishvili, G.; Lomidze, L.; Matiashvili, G.
Abstract : The formation of mid-latitude sporadic-E (Es) layer under the influence of atmospheric gravity waves (AGWs), evolving in the background horizontal wind with a horizontal linear shear (horizontal shear flow), is studied. The AGWs, which are in-situ excited in the horizontal shear flow, interact with metallic ions through ion-neutral collisions and Lorentz forcing, influence the horizontal and vertical motion of ions, and lead to their convergence into thin horizontal layers. In order to investigate the formation of sporadic-E, 2-D numerical simulations are performed and temporal evolution of multilayered sporadic-E is demonstrated. It is found that ion/electron density of Es layer depends on the value of the horizontal shear of a magnetic north-directed background wind. The increase of the shear parameter in the cyclonic type background wind leads to the increase of horizontal convergence of charged particles. It is shown that the plasma density of Es layers also depends on the horizontal and vertical amplitudes of AGWs' velocity perturbations, which increase in the horizontal shear flow and cause a formation of multilayered sporadic-E. The Es layers mainly move downwards, but at certain spatial location, where temporal changes in wave phase caused by background shear flow and AGW are small, these layers are almost horizontal. The vertical spatial location of the horizontal Es layers is determined by the vertical wavelength of atmospheric gravity waves. Highlights: We investigate an influence of horizontal shear flow on ions drift velocities. We investigate an influence of AGWs role on ions drift velocities. Model of Es formation under influence of AGWs evolving in the shear flow. Criteria of heavy metallic ions horizontal convergence under influence of AGWs.